Management Optimism and Corporate Acquisitions: Evidence from Insider Trading - BOEHMER, Ekkehart (Institutional Knowledge at Singapore Management University, 1997)
In this study we integrate evidence about managers' personal beliefs about their firms' prospects into an analysis of managerial decisions on acquisitions and takeover resistance. We examine insider trading (a proxy for personal beliefs) around significant corporate acquisitions and find little cross-sectional differences in the trading patterns of all managers around an acquisition. In general, the insiders do not change their trading patterns in the period when their firm is making an important corporate acquisition. We still obtain this result after controlling for the announcement-day abnormal return. We also find that while managers of firms that do not become takeover targets themselves and of firms that are eventually targets of friendly bids earn positive abnormal returns in the period after their trade, this is not true for managers of firms that are later subject to a hostile bid.